Developing a digital toolkit to enhance the communication of health claims: The Health Claims Unpacked project. Issue 4 (11th December 2020) - Lockyer, S.; Ryder, C.; Jaworska, S.; Benelam, B.; Jones, R.
Abstract: Consumer understanding and acceptance of health claims are influenced by a variety of factors including personal knowledge and familiarity with the information, characteristics of the product (such as the ingredients) and the way the claim is presented ( e.g . wording and visual aids such as symbols). The official wording of authorised EU health claims is set by the European Commission (EC), though there is some flexibility, in that food companies can change the wording to aid consumer understanding of the claim as long as the original meaning is retained and the modified version does not mislead. An EIT Food‐funded project with the consumer‐facing title Health Claims Unpacked, consists of an international consortium aiming to develop a digital toolkit to investigate consumers' responses to health claims and aid their understanding thereof. Developed firstly in English (and now also in other EU languages such as German, French and Polish), the toolkit is informed by research in linguistics, design, nutrition science, technology and behavioural economics as well as focus groups with consumers and interviews with the food industry. The format of the toolkit is an interactive web app comprising activities which are used to gather data regarding consumers' responses to different kinds of linguistic, semiotic (signs and symbols) and marketing cues related to health claims and how these cues impact their understanding of the relationship between nutrients/food components and health, trust in the message and willingness to pay for products. The data will be used to provide information on the preferences of different demographic groups on the wording of health claims and to provide recommendations for stakeholders aiming to enhance the communication of health claims on food and drink labels.